Slotted Secondary Transmission With Adaptive Modulation and Coding Under Interweave Cognitive Radio - Wang, Wen-Jing; Zhang, Hui-Sheng (IEEE transactions on vehicular technology, 2019)
In this paper, we propose a discrete-time Markov model to characterize slotted secondary transmission process under interweave cognitive implementation. Stationary distribution is solved in closed form to evaluate SU-to-PU collision probability and SU successful transmission probability. Assuming that SU transmission adopts adaptive modulation and coding (AMC), we then carry out the queuing analysis in terms of throughput, queuing delay, and packet drop probability, based on a two-dimensional finite-state Markov chain for small-size packet transmission. The optimal length of secondary slot is solved by maximizing throughput subject to an SU-to-PU collision probability constraint. For large-size packet transmission, the probability mass function of extended delivery time for secondary packet transmission is also derived. Selected numerical results are presented to illustrate the mathematical formulas and to validate our research results.